Ôôôô de Casa... Ôôôô de Fora... As cozinhas em Grande Sertão: veredas e a partilha do alimento como hierofania nos gestos sertanejos - Santana, Ursulina Maria Silva (2015)
From the reading of the book Grande Sertão: Veredas by Guimarães Rosa this thesis aims to contribute for the understanding of relationship between food and religion. According to the author s notes where he talks about the presence of food in the country s dry countryside Sertão found in his classical novel, one can realize through Riobaldo s narrative two specific cuisines: the inner cuisine and the outer cuisine. Two different cuisines, within their own characteristics, establishing relationships between people and social groups. The menu is shown during the countryside s journey done by the group and in the sharing moments with those who they meet along their way. Because it is a search in the context of the Science of Religion discipline, the cuisine itself, the cooking practices and the sharing of the meal will be focused on its religious aspect as something that transcend the materiality , constituting in this way a sacred manifestation / appearance. This paper aims to state the importance of the distinct cuisines shown by Riobaldo in his narrative and how they work in their specifities, the utilization and consumption of ingredients. Thus the building of the Brazilian cuisine will allow an understanding of the significant kind of food that created the menu while a mystic from the countryside is perceived from the gestures that are shown and from the relationships that are established while sharing the food